An assessment of road safety knowledge of drivers and community: An impact evaluation of the project intervention - Saha, Polin Kumar (BRAC Research and Evaluation Division, 2022)
The endline study was undertaken by the Research and Evaluation Division of BRAC. Highlighting the aim of BRAC's road safety program of achieving zero fatal road accidents, the existing community-centric knowledge was evaluated. The endline survey assessed the participants from the community-based organizations, community road safety groups, students and drivers of both motor and non-motor vehicles. The respondents of the endline survey were the same as the baseline study area over the one-year project duration. The study intended to understand the project impact on individuals and group level knowledge, attitude level of drivers and community members towards achieving road safety. In order to map changes over time between baseline and end-term periods, the end line study included two groups of respondents – intervention (treatment) and control groups. Findings were mostly quantitative in nature. The project intervention had achieved positive results in some indicators of road safety awareness; e.g. license and other necessary papers of vehicles, driver training, the fitness of vehicles, traffic rules, traffic signs and symbols, and frequency of road accident. On the other hand, the map changes were not found satisfactory in case of obeying the traffic rules and regulations of the drivers, drug or nicotine addiction, and the tendency of receiving mobile phone calsl while driving. The students were very aware of traffic rules and related road safety matters. They gathered knowledge from their teachers mostly, rather than their parents. But the implications of student knowledge were not seen at the field level. The overall community-centric knowledge and awareness of road safety had increased. Some individuals moved alone for road safety issues, because of their community ownership of maintaining roads and road safety at a community level. Finally, the community deserved administrative support along with their own efforts to further improve road safety.